Biomarcadores moleculares e a recuperação funcional no pós-acidente vascular cerebral - Pacheco, Cássia Regina Saade (Universidade Federal de São Carlos, 2020)
Molecular biomarkers have proved important biological signalers, potential markers in the diagnosis and prognosis of stroke. More common in ischemic than hemorrhagic form, generalizing metabolomics and proteomics in both types of stroke can be a mistake, making biomarkers studies for each of them important. Present in biological fluids, such as blood, urine, cerebrospinal fluid and saliva, the biomarker when identified in the acute or chronic phase can assist in immediate actions and in directing the treatment of the disease and in functional physical recovery. Studies had shown that high levels of adiponectin are relayed with sarcopenia and cardiovascular diseases, without strokes, their levels were high in post-stroke levels compared to non-strokes, but it was not associated with skeletal muscle mass. Objectives: To investigate adiponectin levels in body composition, lipid levels and physical activity in chronic stroke. Searching in the literature biomarkers hemorrhagic stroke predictors of prognosis of functional physical recovery. Methodology: Two studies were conducted: 1) A correlational cross-sectional pilot study with chronic hemipartic (stroke ≥ 6 months), age ≥ 18 years, for analysis of body mass by electrical bioimpedance (InBody® 720) and lipid profile with analysis by automated method (CELL-DYN Ruby); activity level measured by accelerometer (StepWatch®) and serum adiponectin concentration using enzyme immunoabsorption assay kit (ELISA). 2) Systematic peer review, following prisma recommendations in PubMed, CINAHL, Web OF Science and EMBASE databases. A search was made for studies with hemorrhagic stroke and molecular biomarkers present in the blood, urine, saliva and cerebrospinal fluid, collected up to 72 hours post-icto, linked to functional recovery. Results: The ADPc study included 21 post-stroke participants who had the biomarker correlated with: weight (rs = -0.73), body mass index (rs = -0.50), skeletal muscle mass (rs = -0.78), skeletal muscle mass index (rs = -0.75) and high-density lipoprotein (rs = 0.43). The search for a systematic review gathered 61 studies and 79 biomarkers, 52 biomarkers considered predictors, 18 non-predictors and 9 with controversial results. Conclusion: Adiponectin at high levels is related to decreased skeletal muscle mass and a higher level of high-density lipoprotein in chronic post-stroke individuals. Most of the biomarkers found with the possibility of predicting functional recovery after hemorrhagic stroke did not present clear recommendations for the identification of the most promising and consistent biomarker due to the heterogeneity of the molecules studied.
Molecular biomarkers and functional recovery after stroke
Keywords: Biomarcador; Adiponectina; Acidente vascular cerebral; Prognóstico; Funcionalidade; Músculo esquelético; Lipoproteínas de alta densidade lipídica; Atividade física; Biomarker; Adiponectin; Stroke; Prognosis; Functionality; Skeletal muscle; High-density lipoproteins; Physical activity; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL